Development Imperatives for the Asian Century - Peter Petri; Vinod Thomas (Asian Development Bank (ADB), 2013)
Evidence-based economic policies - pragmatic policies that work - played a major role in Asia's success in raising its living standards in the last half century. However, growth prospects are now threatened by rising income inequality and environmental degradation if Asia continues on its established growth path. Evidence strongly argues for Asia to broaden its development priorities into a triple bottom line: that is, a focus on growth, social inclusion, and environmental sustainability. The paper focuses on how Asia can manage this ambitious goal. Possible resistance from vested interests is to be anticipated, but pursuing this path could bring large overall gains. The paper looks at how Asian governments and their development partners can make a difference in promoting the three policy objectives. Innovations in governance for better accountability, transparency, and feedback will be necessary for achieving these priorities. Societies in Asia and the international community will also need rigorous evidence and analysis to establish the benefits of this strategy and to make informed policy choices. International financial institutions and the donor community can provide financial lubricants for cooperation, as well as knowledge to help governments counter vested interests and champion regional perspectives on transborder issues. Reversing the negative social and environmental trends has to become a real development priority rather than a mere aspiration. Progress is possible on the three bottom-line goals, but it will require focusing Asia's vaunted methods of learning and innovation to meet the new challenges.
hdl:11540/2309
Keywords: D62; E02; F64; O19; O44; 330; videnced-based policy; governance; institutions; inclusive growth; Kuznets curve; sustainability